TES INVENTORY PERSONAL SURVEY (TIPES) SEBAGAI REKOMENDASI PEMILIHAN JURUSAN SEKOLAH MENENGAH KEJURUAN - Agus Aan Jiwa Permana; Ni Wayan Marti; Kadek Suranata (Jurnal Teknologi Informasi dan Komputer, 2018)
ABSTRACTIn developing superior human resources, it takes a long time, is focused, and requires support from all components of society. We can see developing and developed countries having reliable human resources both in the fields of technology, agriculture, maritime affairs and tourism. The current big challenge to support the development of the creative economy is closely related to increasing the quantity and quality of vocational education (vocational) to be able to compete globally. The Specialization Test used during the selection of new students can provide an alternative selection of majors to new students in accordance with the competencies they have, so that the system issues a choice of department recommendations in accordance with their competencies. This is the basis for implementing the system as an initial filter for selection of students having competencies with appropriate interests then through the education process to face the fourth industrial revolution (i4.0). With initial selection through the TIPES system, expectations are in line with the 2010-2014 Ministry of Education and Culture RENSTRA, namely 70% of SMK graduates work in the graduation year and all SMKs providing entrepreneurship development coaching services can be realized.Keywords: superior human resources, creative economy, global competing vocational, majors selection recommendationsABSTRAKDalam mengembangkan SDM yang unggul memerlukan waktu yang cukup lama, terfokus, serta memerlukan dukungan dari seluruh komponen masyarakat. Kita bisa lihat negara yang sedang berkembang dan maju memiliki SDM yang handal baik di bidang teknologi, pertanian, kelautan, dan pariwisata. Tantangan besar saat ini untuk menunjang pengembangan ekonomi kreatif sangat berhubungan dengan meningkatkan kuantitas dan kualitas pendidikan kejuruan (vokasi) untuk mampu bersaing secara global. Test Peminatan yang digunakan saat seleksi siswa baru dapat memberikan alternatif pemilihan jurusan kepada siswa baru sesuai dengan kompetensi yang mereka punya, sehingga sistem mengeluarkan rekomendasi pilihan jurusan sesuai dengan kompetensinya. Hal inilah yang menjadi dasar untuk mengimplementasikan sistem sebagai saringan awal untuk seleksi siswa memiliki kompetensi dengan minat yang sesuai kemudian melalui proses pendidikan untuk menghadapi revolusi industri keempat (i4.0). Dengan seleksi awal melalui sistem TIPES, maka harapan sesuai dengan RENSTRA Kemendikbud 2010 – 2014 yaitu 70% lulusan SMK bekerja pada tahun kelulusan dan seluruh SMK menyediakan layanan pembinaan pengembangan kewirausahaan dapat terwujud.Kata Kunci : SDM handal, Ekonomi kreatif, Vokasi bersaing global, Rekomendasi pemilihanjurusan